Okak, Schulkinder am Hospital 1912 - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of Inuit school children sitting on the steps of the hospital in Okak, 1912. Black and white photograph of Inuit school children sitting on the steps of the hospital in Okak, 1912.